Fast parameter extraction of voxelized interconnects and circuits - Wang, Mingyu (Nanyang Technological University, 2022)
Recent stunning developments in three-dimensional (3-D) printing technology have allowed the designers to produce their circuit boards and components at the convenience of their own laboratories. Such production potentially reduces the prototype development time from weeks to hours and is thereby expected to be widely preferred by the designers. The 3-D printers build the circuits/structures voxel by voxel (i.e., cube by cube). Therefore, the analysis and design tools that can be operated on the voxel-based discretizations are called for. Furthermore, virtual fabrication environments developed for modeling unit process steps of the semiconductors and micro-electro-mechanical systems are primarily voxel-based. By using these environments, the designers can iteratively explore their designs; they can alter their designs and check whether their designs meet certain design specifications. To check the performance of their designs, the designers are in need of electromagnetic (EM) simulators that can be used in conjunction with these virtual fabrication environments and operated on interconnects/circuits/structures discretized by voxels. Unfortunately, the current literature lacks studies on the development of such EM simulators. To fill this gap, three open source EM simulators that can be operated on voxelized interconnects/circuits/structures are proposed in this thesis.